Problem-Based Learning Management about Online Human Rights for Enhancing Digital Empathy Skills of Secondary School Year 3 Students in Special Large-Sized Schools in Phitsanulok Province - Sri-in, Chonticha; Sriphan, Atchara (Journal of Buddhist Education and Research (JBER), 2025)
This qualitative research aimed to: 1) investigate the current conditions and problems of learning management using problem-based learning (PBL) on online human rights to enhance digital empathy skills of secondary school year 3 students in special large-sized schools in Phitsanulok Province; and 2) develop learning management using PBL on online human rights to foster digital empathy skills among the same student group in special large-sized schools in Phitsanulok Province. The participants comprised 44 individuals, including 4 teachers from the Social Studies, Religion and Culture learning area, and 40 secondary school year 3 students. Data were collected through document analysis, interviews, and observation. The credibility of the data was ensured through triangulation, and data analysis was performed using inductive reasoning. The research findings revealed that regarding the current conditions and problems, it was found that: teachers lacked proficiency in using technological media; students demonstrated insufficient awareness of online expression; the content did not comprehensively cover online human rights; learning materials were outdated and failed to engage students; learning activities, such as lectures, did not promote critical thinking and problem-solving skills; assessment, relying solely on tests, proved inadequate for measuring digital empathy; and the technological environment was not conducive to learning. The development of learning management on online human rights to enhance digital empathy skills revealed that: teachers respected individual differences and provided students with opportunities for free expression; students became aware of human rights and practiced ethical online behavior; the learning content comprehensively covered the principles of online human rights; media derived from real-life events enhanced understanding of others' perspectives and emotions; learning activities fostered thinking and knowledge exchange; assessment methods were diverse and capable of reflecting online behavior; and the learning environment facilitated the development of digital empathy skills in three dimensions: 1) cognitive empathy: students respected diverse opinions and supported equitable freedom of expression; 2) emotional empathy: students recognized the impact of cyberbullying and demonstrated empathy towards victims; and 3) compassionate empathy: students promoted the use of technology to aid society and exhibited responsible online behavior.